Margarita Wednesdays [large type] : making a new life by the Mexican sea - Rodriguez, Deborah (Center Point Large Print, 2014)
"Deborah Rodriguez's memoir of her journey of self-discovery and renewal after she was forced to flee Afghanistan in 2007"--